Influence of Oil-Soluble Catalyst on Composition and Structure of Heavy Oil from Samara Region Field - Mohammed O. N. Ali; Irek I. Mukhamatdinov; Boudkhil Affane; Rezeda E. Mukhamatdinova; Vladimir E. Katnov; Alexey V. Vakhin (ChemEngineering)
In this study, an examination was conducted of the influence of iron tallate on the composition and properties of highly viscous oil from the Strelovskoye deposit in the Samara region under thermal–catalytic treatment (TCT). The research revealed that the dynamic viscosity of the oil following TCT at 300 °C, with a measurement temperature of 20 °C, decreased by a factor of 8 in comparison to the initial sample and nearly 4.5 times compared to the control sample at the 96-h mark. The most promising results in reducing the pour point temperature to 7 °C were identified following a 96-h TCT at 300 °C. This reduction was attributed to the decrease in paraffin content facilitated by the presence of the catalyst. According to the ICP-MS results, the extraction of the catalyst with the oil amounted to only 1%. This indicates that during the implementation of TCT within the reservoir, the catalyst is likely to adsorb onto the rock surfaces.